Die Untersuchung der Struktur sozialer Räume - Moch, K.-J.; Killisch, W.F. (ERDKUNDE, 1975)
Social geography has recently concentrated more in tensely on the exploration of the structure of social systems. Methods are being applied which are exclusively developed for the analysis of social stratification. We question these methods commonly used by social research and we point out that none of them can lay claim to being scientifically convincing. As the reason is the lack of methodological foundation some basic remarks are necessary before we develop a general theory of the structure of social systems. Thereafter we consider a statistical procedure suited for the analysis of these structures. As an example we finally should like to put forward some findings in social statistics which have been obtained from an analysis of an urban renewal area.